'Railroad switch' technique for stent-assisted coil embolization of a wide-neck bifurcation intracranial aneurysm: technical note. Issue 4 (August 2020) - Heiferman, Daniel M; Reynolds, Matthew R; Reddy, Arra S; Serrone, Joseph C
Preservation of the posterior cerebral arteries during endovascular treatment of wide-neck basilar bifurcation aneurysms remains a technical challenge despite recent device innovations. We present a novel stent deployment technique, the 'railroad switch', to protect both posterior cerebral arteries during treatment of a recurrent basilar bifurcation aneurysm. Following asymmetric basilar–posterior cerebral artery stent deployment, favoring distal placement in a posterior cerebral artery, advancement of a jailed microcatheter will advance the proximal stent into the aneurysm, protecting both posterior cerebral arteries and the native basilar terminus. This novel maneuver offers interventionalists another application of commonly used intracranial stents for endovascular management of complex basilar bifurcation aneurysms.